Immunological Effects of Dimethyldioctadecylammonium Bromide and Saponin as Adjuvants for Outer Membrane Vesicles from Neisseria meningitidis - Victor Araujo Correa; Amanda Izeli Portilho; Elizabeth De Gaspari (Diseases, 2022)
The meningococcal disease is a global health threat, but is preventable through vaccination. Adjuvants improve meningococcal vaccines and are able to trigger different aspects of the immune response. The present work evaluated the immune response of mice against Neisseria meningitidis outer membrane vesicles (OMV) complexed with the adjuvants aluminium hydroxide (AH), via subcutaneous route; and dimethyldioctadecylammonium bromide (DDA) or Saponin (Sap), via intranasal/subcutaneous routes. ELISA demonstrated that all adjuvants increased IgG titers after the booster dose, remaining elevated for 18 months. Additionally, adjuvants increased the avidity of the antibodies and the bactericidal titer: OMVs alone were bactericidal until 1:4 dilution but, when adjuvanted by Alum, DDA or Sap, it increased to 1/32. DDA and Sap increased all IgG isotypes, while AH improved IgG1 and IgG2a levels. Thus, Sap led to the recognition of more proteins in Immunoblot, followed by DDA and AH. Sap and AH induced higher IL-4 and IL-17 release, respectively. The use of adjuvants improved both cellular and humoral immune response, however, each adjuvant contributed to particular parameters. This demonstrates the importance of studying different adjuvant options and their suitability to stimulate different immune mechanisms, modulating the immune response.